2015
DOI: 10.1007/s12031-015-0576-8
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of Brain Proteinase-Activated Receptor-2, Trypsin-2 and Serpin Proteinase Inhibitors in Parkinson’s Disease

Abstract: In neurologically normal brain expression of proteinase-activated receptor-2, activating proteinases and proteinase inhibitors was found in neurons and microglia and did not specifically associate with regions prone to neurodegeneration in Parkinson's disease. InParkinson's disease brain, alterations in the amount of immunoreactivity for proteinaseactivated receptor-2, trypsin-2 and both serpin proteinase inhibitors were found throughout the brain. In neurons, there was a decrease in neurons positive for prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 50 publications
0
16
1
Order By: Relevance
“…On the other hand, prodromal alterations in motor cortex plasticity are supported by pathological investigations on Ca 2+ channels, which are critical in the regulation of cortical excitability and plasticity (Wankerl et al, 2010;Verhoog et al, 2013;Weise et al, 2017). Specifically, recent postmortem studies show increased expression of L-type voltagegated Ca 2+ channels in the primary motor cortex at least as early as Braak's stages III-IV (Hurley et al, 2013(Hurley et al, , 2015b, and molecular alterations in motor cortical areas have also been reported in incidental Lewy body disease at Braak's stages I-II (Hurley et al, 2015a;Santpere et al, 2018). Motor cortical areas thus seem to be altered well before the appearance of cortical Lewy pathology (Braak's stages V-VI) and before the onset of motor features in PD.…”
Section: Evidence For Primary Cortical Involvement In Parkinson's Dismentioning
confidence: 95%
“…On the other hand, prodromal alterations in motor cortex plasticity are supported by pathological investigations on Ca 2+ channels, which are critical in the regulation of cortical excitability and plasticity (Wankerl et al, 2010;Verhoog et al, 2013;Weise et al, 2017). Specifically, recent postmortem studies show increased expression of L-type voltagegated Ca 2+ channels in the primary motor cortex at least as early as Braak's stages III-IV (Hurley et al, 2013(Hurley et al, , 2015b, and molecular alterations in motor cortical areas have also been reported in incidental Lewy body disease at Braak's stages I-II (Hurley et al, 2015a;Santpere et al, 2018). Motor cortical areas thus seem to be altered well before the appearance of cortical Lewy pathology (Braak's stages V-VI) and before the onset of motor features in PD.…”
Section: Evidence For Primary Cortical Involvement In Parkinson's Dismentioning
confidence: 95%
“…We validated the relevance of the identified BRGs to PD progression with two datasets of non-neurological controls (Genotype-Tissue Expression project (GTEx) 19 and UK Brain Expression Consortium (UKBEC) 20 ) and two datasets of PD donors. We found altered expression patterns in patients with PD and incidental Lewy body disease (iLBD), who are assumed to represent the pre-clinical stage of PD 11,21 . In non-neurological brains from the AHBA, we further identified modules of co-expressed genes across Braak LB stage involved regions, and characterized them functionally by assessing their enrichment for cell-type markers, gene ontology (GO)-terms, and disease-associated genes.…”
Section: Introductionmentioning
confidence: 99%
“…We validated our findings in two independent non-neurological datasets (the Genotype-Tissue Expression project (GTEx) 19 and UK Brain Expression Consortium (UKBEC) 20 ). Further, we showed that Braak stage-related genes (BRGs) are indeed progressively disrupted in patients with incidental Lewy body disease (iLBD; assumed to represent the pre-clinical stage of PD 11,21 ) and PD. The observed transcriptomic signatures of vulnerable brain regions pointed towards the dopamine biosynthetic process and oxygen transport that were highly expressed in brain regions related to the preclinical stages of PD.…”
mentioning
confidence: 99%